Role of palliative care in centers performing maternal–fetal interventions - Rholl, Erin; Leuthner, Steven R. (Frontiers in Pediatrics, 2023)
Advancements in maternal-fetal interventions have allowed for direct fetal access shifting the focus of interventions from maternal health for fetal health to a focus on sole fetal/neonatal benefit. Given that access to the fetus can only be obtained through the mother, there are ethical considerations important to consider when counseling the maternal-fetal dyad. Goals of maternal-fetal interventions range from improved fetal/neonatal survival to decreased long term morbidities and improved quality of life. However, interventions with the goal of improving quality of life may not always achieve their desired result. Additionally, maternal-fetal interventions have risks such as premature birth and other complications that should be heavily considered as they may offset potential benefits of the procedure. While some families elect for a maternal-fetal intervention, doing every potential postnatal intervention may not be in alignment with their goals depending on the outcome of the intervention. Given the complex, value laden decision making that is crucial to counseling parents about decisions surrounding maternal-fetal interventions and subsequent neonatal care, palliative care specialists should be utilized in fetal centers. Palliative care specialists are trained to assist with complex, goal concordant decision making and can guide families and medical teams through the decision points that arise during the treatment journey.